ANALYSIS OF STUDENTS' CRITICAL THINKING SKILLS IN MATHEMATICS LEARNING CLASS V SDN 1 PEUKAN BADA - Tria Marvida; Raziska Ibrahimi; Raudha Meutia (International Conference on Education, Science, Technology and Health (ICONESTH), 2024)
Students need to be trained in high-level thinking skills in order to be able to build an understanding of mathematics and be able to solve it. Based on the results of observations, there are still many students who are not active in the learning process, for example they do not ask teachers about the material being taught. The purpose of the study is to determine the critical thinking ability of students in solving problems in fractions. The type of research used is descriptive with a qualitative approach. Observation, tests and interviews are the methods used to collect data. The research data was analyzed using the Miles and Huberman model. The results of the study showed that the critical thinking ability of grade V students of SDN 1 Peukan Bada in solving fractional problems was divided into three categories, namely high, medium and low. Students think highly with a figure of 16%. Students have medium thinking skills of 8% and low 76%.